1999
DOI: 10.1038/9035
|View full text |Cite
|
Sign up to set email alerts
|

Indirubin, the active constituent of a Chinese antileukaemia medicine, inhibits cyclin-dependent kinases

Abstract: Indirubin is the active ingredient of Danggui Longhui Wan, a mixture of plants that is used in traditional Chinese medicine to treat chronic diseases. Here we identify indirubin and its analogues as potent inhibitors of cyclin-dependent kinases (CDKs). The crystal structure of CDK2 in complex with indirubin derivatives shows that indirubin interacts with the kinase's ATP-binding site through van der Waals interactions and three hydrogen bonds. Indirubin-3'-monoxime inhibits the proliferation of a large range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
625
3
17

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 758 publications
(675 citation statements)
references
References 17 publications
17
625
3
17
Order By: Relevance
“…The bis-indole alkaloid indirubin is an active ingredient of a traditional Chinese medical preparation that exhibits anti-inflammatory activity and antileukemic activity against myelocytic leukemia (Hoessel et al, 1999). Indirubin and particularly indirubin derivatives such as indirubin-3 0 -monoxime and indirubin-5-sulfonate, which have low toxicity, have been considered as anticancer agents (Hoessel et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bis-indole alkaloid indirubin is an active ingredient of a traditional Chinese medical preparation that exhibits anti-inflammatory activity and antileukemic activity against myelocytic leukemia (Hoessel et al, 1999). Indirubin and particularly indirubin derivatives such as indirubin-3 0 -monoxime and indirubin-5-sulfonate, which have low toxicity, have been considered as anticancer agents (Hoessel et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Indirubin and particularly indirubin derivatives such as indirubin-3 0 -monoxime and indirubin-5-sulfonate, which have low toxicity, have been considered as anticancer agents (Hoessel et al, 1999). Indirubin and its derivatives have been described as selective inhibitors of cyclin-dependent kinases (CDKs) such as CDK1/ cyclin B, CDK2/cyclin A, CDK2/cyclin E and CDK5/ p25 (Hoessel et al, 1999;Davies et al, 2001;Marko et al, 2001;Jautelat et al, 2005). It has been reported that these compounds are able to inhibit the proliferation of a variety of cultured cell types by a block in the G1/S or the G2/M phase of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…600 metaphases were scored for RI, and 6000 metaphases were scored for the MI; RI replication index, MI mitotic index, M 1, M 2 and M 3 metaphases 1, 2 and 3, respectively, Na 2 S 2 O 4 Sodium dithionite, MMC mitomycin-C, AE antigenotoxic and anti cancerogenic in Traditional Chinese Medicine. Hoessel et al (1999) reported that indirubin exhibited no toxic effect on bone marrow even in long-term studies. Also synthetic indirubin was reported to be a good antitumour agent and had only minor toxicity in animal models (Hoessel et al 1999).…”
Section: Sister-chromatid Exchange (Sce) and Mitotic Indices (Mi) Resmentioning
confidence: 99%
“…Hoessel et al (1999) reported that indirubin exhibited no toxic effect on bone marrow even in long-term studies. Also synthetic indirubin was reported to be a good antitumour agent and had only minor toxicity in animal models (Hoessel et al 1999). Mutagenic effect of the natural chemicals and some Isatis sp.…”
Section: Sister-chromatid Exchange (Sce) and Mitotic Indices (Mi) Resmentioning
confidence: 99%
See 1 more Smart Citation